Does the director labor market offer ex post settling-up for CEOs? The case of acquisitions - Harford, Jarrad; Schonlau, Robert J. (Journal of Financial Economics, 2013)
We examine the rewards for experience and ability in the director labor market. We show that large acquisitions are associated with significantly higher numbers of subsequent board seats for the acquiring CEO, target CEO, and the directors. We also find that, in the case of acquisitions, experience is more important than ability. Both value-destroying and value-increasing acquisitions have significant and positive effects on a CEO's future prospects in the director labor market. In addition to increasing our understanding of the director labor market, these results suggest that the ex post settling-up incentives thought to exist in the director labor market are weak for acquisitions.